2013
DOI: 10.1182/blood.v122.21.5137.5137
|View full text |Cite
|
Sign up to set email alerts
|

Resistance To Vorinostat In Hematological Malignancies May Involve Cytoprotective UPR and Correlates With Increased Sensitivity To Bortezomib-Induced Cell Death

Abstract: Histone deacetylase inhibitors (HDACi) have shown promising activity against hematological malignancies in clinical trials and have led to the approval of vorinostat for the treatment of cutaneous T-cell lymphoma. However, as with many cancer therapies, de novoresistance is common and acquired resistance inevitably follows sensitivity. This issue is particularly difficult to resolve in HDACi therapy, as the mechanism of action is still unclear and may involve several components. Our objective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The ability of these EMTs to reverse aberrant epigenetic marks and re-sensitize or ‘epi-sensitize’ some tumors to treatments to which they had acquired resistance, [ 10 – 12 ] makes them an attractive therapeutic avenue for further development. Although this re-sensitizing effect is seen in some instances, this is not always the case as a number of studies have reported [ 13 , 14 ]. None-the-less, their perceived reduced toxicities make it an attractive option for patients unfit for the current more toxic regimens [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 95%
“…The ability of these EMTs to reverse aberrant epigenetic marks and re-sensitize or ‘epi-sensitize’ some tumors to treatments to which they had acquired resistance, [ 10 – 12 ] makes them an attractive therapeutic avenue for further development. Although this re-sensitizing effect is seen in some instances, this is not always the case as a number of studies have reported [ 13 , 14 ]. None-the-less, their perceived reduced toxicities make it an attractive option for patients unfit for the current more toxic regimens [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 95%